ANALISIS VARIAN ANGGARAN OPERASIONAL PADA PERUMDA TIRTA PAKUAN KOTA BOGOR - Suprobo, Rien Evangelin; Manullang, Asna (STIE PENA, 2023)
This research aims to find out whether there are deviati The analytical method used is a descriptive method, namely a research method that only describes the analysis of the company's operational budget so that it can be seen between the budget that has been prepared and agreed with the realization in the field ons between the opeand to find out the causes of operational budget deviations and their realization in the Tirta Pakuan Regional Government of Bogor City rational budget and its realization. The results of research from the analysis of operational budget variances at Perumda Tirta Pakan, Bogor City, show that there are deviations between income and operational costs, whether unprofitable deviations or profitable deviations. control over revenue is still not optimal (unfavorable) at 0.24 due to the company's targets not being achieved, whereas in terms of operational costs at the Perumda Tirta Pakan company it is effective, this is due to improvements made by the company on any costs where irregularities occur. keywords: Deviation; operational budget; variance analysis.